2017
DOI: 10.1016/j.eucr.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Renal Leiomyoma: A Case Report and Review of the Literature

Abstract: Leiomyoma is an uncommon tumor of the kidney. The authors report a rare case of renal leiomyoma in a 39-year-old male patient who presented with a right flank mass. Laparoscopic nephrectomy was performed. The histopathology and immunohistochemistry confirm the diagnosis of renal leiomyoma. The review of literature in the clinicoradiopathological correlation was illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 3 publications
(10 reference statements)
0
11
1
Order By: Relevance
“…Leiomyoma which is the most common benign tumor of the genital tract in women of reproductive age, may rarely arise from almost any part of the genitourinary system. 1 , 2 , 3 , 4 , 5 Renal leiomyoma is extremely rare benign lesion originating from the tunica media layer of renal cortical vascular structures or smooth muscle cells in the renal capsule or renal pelvis, which can be usually classified as subcapsular, capsular, or subpelvic type, respectively. 1 , 2 , 3 , 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leiomyoma which is the most common benign tumor of the genital tract in women of reproductive age, may rarely arise from almost any part of the genitourinary system. 1 , 2 , 3 , 4 , 5 Renal leiomyoma is extremely rare benign lesion originating from the tunica media layer of renal cortical vascular structures or smooth muscle cells in the renal capsule or renal pelvis, which can be usually classified as subcapsular, capsular, or subpelvic type, respectively. 1 , 2 , 3 , 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…Renal leiomyomas are usually detected incidentally in adults with a female predilection (2:1) and the average age has been reported as 47. 1 , 2 , 3 , 4 , 5 These tumors constitute 1.5% of benign renal tumors and 0.3% of overall renal tumors. 5 It has been reported that it is seen in the rate of 4.2–5.2% in autopsy series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leiomyomas are infrequent solid, benign lesions of the kidney which arises from smooth muscle cells of various structures of kidney such as renal capsule, pelvis or vascular smooth muscle (1). In spite of their rarity within the genitourinary system, leiomyomas are frequently detected in the kidneys and are less often non-epithelial benign tumors of the bladder (2).…”
Section: Introductionmentioning
confidence: 99%
“…The differential diagnosis can be difficult with clinical evaluation. Therefore, a variety of immunohistochemical staining methods such as cytokeratin, S100, Mart1 and HMB45 are needed for the definitive diagnosis of leiomyoma (1).…”
Section: Introductionmentioning
confidence: 99%